Enantiomeric separation of Midodrine hydrochloride in bulk and pharmaceutical dosage form by chiral HPLC - Jenifer Ashwini S; Narenderan ST; Meyyanathan SN; Babu B; Gowramma B (International Journal of Research in Pharmaceutical Sciences, 2019)
A simple, sensitive chiral liquid chromatographic method was developed for the separation and quantification of enantiomers Midodrine. A chiral PAK IG3 (150 x 4.6 mm) 3µm column was used for the separation of the enantiomers. The mobile phase consists of 10 mM ammonium bicarbonate in water and acetonitrile in the ratio of 95:5, v/v with a flow rate of 0.7 ml/min. The detection was done at 290 nm with column temperature maintained at 40°C. The method linear ranged between 10 – 110 μg/ml and 5 – 100 μg/ml for (+) and (-) Midodrine enantiomers. The recovery of the method was found to be in the range of 99.1 to 101.2 %. The detection limit for the (+) and (-) enantiomers was found to be 4 μg/ml and 1 μg/ml, respectively. A simple validated chiral HPLC method with reverse elusion is described for the separation and quantification of the enantiomers of Midodrine in bulk and formulation.